Effect of frequency scaling granularity on energy-saving strategies. (July 2019) - Sundriyal, Vaibhav; Keipert, Kristopher; Sosonkina, Masha; Gordon, Mark S
Energy efficiency and energy proportional computing have become major constraints in the design of modern exascale platforms. Dynamic voltage and frequency scaling (DVFS) is one of the most commonly used and effective techniques to dynamically reduce power consumption based on workload characteristics. Many energy-saving strategies, however, employ DVFS without considering its applicability level in a given multicore processor. The present work demonstrates that disregarding the DVFS granularity as a design constraint while developing energy-saving strategies may reduce the efficacy of the strategy for certain application classes. Specifically, DVFS applicability levels (called granularities) are determined here for three different Intel processor microarchitectures. Then, the degradation in energy savings is evaluated if the DVFS granularity is disregarded. Experiments were conducted on the widely used quantum chemistry packages, General Atomic and Molecular Electronic Structure System (GAMESS) and NWChem, and show that, for granularity unaware energy-saving techniques, the overall energy consumption may increase by as much as 19%.